“It all just fits together…”: the intersection of language, literacy, and place for adolescents negotiating their identities - Campbell, Morgan M. (Kansas State University, 2012)
This study analyzes the power of literacy and language in adolescent negotiation of identity, particularly in a classroom setting. The theoretical notion of discourse communities provides the framework for this qualitative, narrative case study of one high school junior and her literacy and language experiences from the perspective of her own video diaries. The study applies Critical Discourse Analysis and sociocultural theory to literacy in order to better understand the identity choices students make as they navigate different spaces in their lives. In addition, this study offers several implications for the education profession in regard to the English language arts curricula and new teaching standards. Four emergent themes resulted from analyzing the case study’s video diaries and interviews: 1) Anna uses social languages to enact different identities; 2) Anna’s agency is affected by her assigned identities; 3) language acts as a means of moving between contexts; and 4) language is more than just words. This project sought to understand how Anna’s literacy and language practices are embedded in her sociocultural experiences, and how these experiences and practices shape identity and reconfigure moments of agency and power in the process of negotiating identities across discourse communities. The results of the study indicate that classroom spaces do not always adjust their context to meet the needs of the student, and for Anna, making identity choices to move between contexts did not always mediate success. In essence, language influences opportunities to learn, and our social and cultural position in society, to some extent, determines our success.
Keywords: Language; Literacy; Identity; Adolescent; Education, General (0515)